Students’ Attitude and Perception Towards the Development of Virtual Tour Learning Content in English for Hotel and Tourism Course - Kosasih, Fauzy Rahman; Budiman, Rahmat; Warsihna, Jaka; Ramdani, Zulmi; Pratama, Erik Yudha; Kurniawan, Ramdhan (Universitas Muhammadiyah Malang, 2024)
The massive progress of technology has brought learning into a more practical, interesting, and fun scheme. The presence of virtual tour learning in education is still limited, yet if implemented in a course, such as English for Hotel and Tourism, it might be a new approach to achieving optimal learning experiences. This study aims to explore attitudes and perceptions of users regarding the urgency of developing virtual tour learning content in the course of English for Hotel and Tourism. The study employs a convergent mixed approach by elaborating quantitative and qualitative simultaneously. A total of 69 respondents involved in this study were selected using a purposive sampling technique. The results show that the majority of the respondents considered it important to use virtual tour learning in this course. This perspective can be seen from their attitudes along with various psychological aspects that support the significance of developing such media. In addition, there are many factors that must be considered to get relevant media, including attractive and user-friendly features, providing significant benefits to respondents, and containing guidelines that are relevant to the English for Hotel and Tourism course.